Effective Tax Rate of Sharia Banks in Indonesia: How Profitability Moderates the Effect of Mergers, Size, and Leverage - Tiena Suhartini; Lela Nurlaela Wati; Faizul Mubarok (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The role of taxes is very important for state revenue, but the tax avoidance practices that occur are very detrimental to the state. This research aims to analyze tax avoidance practices, proxied by the effective tax rate (ETR), coinciding with Sharia bank merger momentum, which affects size and leverage with profitability’s moderating effects. Purposive sampling method, determining merged Sharia banks as research samples. This study uses cross-sectional data from Sharia banks’ quarterly financial reports (2015-2022), analyzed with moderated regression analysis. The results show that mergers, size, leverage, and profitability simultaneously significantly influence ETR. Partially, mergers and company size have no negative effect on ETR. Leverage and profitability have a significant negative effect on ETR. Profitability significantly strengthens the negative effect of leverage on ETR but not the effect of mergers and size on ETR. The research highlights the importance of tax strategies in the context of mergers and bank profitability, emphasizing the need to understand the tax impact of mergers. The research underscores the Sharia banks' crucial role in contributing taxes to state revenues. The results provide valuable guidance for Sharia bank management and tax agencies in optimizing the tax contribution from Sharia banks in Indonesia.